2003
DOI: 10.17016/bulletin.2003.89-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in U.S. Family Finances: Evidence from the 1998 and 2001 Survey of Consumer Finances

Abstract: Data from the Federal Reserve Board's Survey of Consumer Finances show a striking pattern of growth in family income and net worth between 1998 and 2001. Inflation-adjusted incomes of families rose broadly, although growth was fastest among the group of families whose income was higher than the median. The median value of family net worth grew faster than that of income, but as with income, the growth rates of net worth were fastest for groups above the median. The years between 1998 and 2001 also saw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(54 citation statements)
references
References 0 publications
2
46
1
1
Order By: Relevance
“…Results showed that students from lower income families had a higher financial literacy compared to their peers from high-income families. This was contradictory to previous research that showed that children from families with adequate and plenty of financial resources were more financially literate than those that came from families that had less financial resources (Aizcorbe et al, 2003; Mandell, 2008). A possible explanation for this difference could be that poor families focus more on saving, budgeting, and planning in order to run their families on a meager income and hence show greater financial literacy.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Results showed that students from lower income families had a higher financial literacy compared to their peers from high-income families. This was contradictory to previous research that showed that children from families with adequate and plenty of financial resources were more financially literate than those that came from families that had less financial resources (Aizcorbe et al, 2003; Mandell, 2008). A possible explanation for this difference could be that poor families focus more on saving, budgeting, and planning in order to run their families on a meager income and hence show greater financial literacy.…”
Section: Discussioncontrasting
confidence: 98%
“…Females and younger populations in the United States have been found to have lower financial literacy levels (Lusardi and Mitchell, 2011). Financial literacy levels have been found to differ by family income, with children from higher income families having higher financial literacy (Aizcorbe et al, 2003). Those without a college degree had lower financial literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Even though at subsistence levels the potential for saving for retirement is small (Masson et al ., 1998), theoretical models often fail to explain saving patterns in low-income individuals. A number of studies, mainly in the US, show that while low-income households may be saving for key life events such as births, marriages and illnesses, the lack of easy access to basic financial services is an important factor in preventing them from saving for retirement (see Dunham, 2001; Vermilyea and Wilcox, 2002; Aizcorbe et al ., 2003; Han and Sherraden, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, research shows that youth and adults in the United States have disturbingly low levels of economic, financial, and consumer literacy (Kotlikoff & Bernheim, 2001). Aizcorbe et al (2003) conclude that the percentage of unbanked families was much higher for low-income, younger, non-White, or Hispanic families. Two common indicators that families are overburdened by debt are a ratio of debt payment to income greater than 40% and being substantially late with credit card payments.…”
Section: Literature Review On Retirement and Financial Securitymentioning
confidence: 80%